Analysis of electricity generation options for sustainable energy decision making: The case of Turkey - ÇİFTÇİOĞLU, GÖKÇEN ALEV; YILAN, GÜLŞAH (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Sustainable energy decision making requires the comparison of energy generation technologies regarding a wide range of economic, technical, environmental, and socio-economic criteria. This study aims to rank the main seven electricity generation technologies for Turkey according to their performance scores. These energy generation technologies are natural gas, coal, hydropower with dam, run-of-river type hydropower, onshore wind, geothermal and solar PV. The sustainability scores are calculated via twelve indicators classified into abovementioned four criteria groups. Multi-criteria decision analysis methodology is employed with a weighted sum multi-attribute utility approach for five different sensitivity cases. The results reveal that the hydroelectric technology with dam is the best option for most of the sensitivity cases. We hope this study gives a scientific and objective standpoint to decision-maker authorities in Turkey for planning sustainable electricity generation policies. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Electricity generation; Energy decision making; Multi-criteria decision analysis; Sustainability; Turkey; MULTICRITERIA ANALYSIS; POWER-PLANTS; TECHNOLOGIES; SCENARIOS; MCDM; RESOURCES; SYSTEMS